Pulmonary Hypertension and Lung Transplantation - Kruszona, Sophie; Aburahma, Khalil; de Manna, Nunzio Davide; Bobylev, Dmitry; Ruhparwar, Arjang; Kuehn, Christian; Salman, Jawad; Ius, Fabio (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2025)
Pulmonary artery hypertension (PAH), a subtype of pulmonary hypertension, is a rare end-stage lung disease. Bilateral lung and combined heart and lung transplantation have long been considered as a gold standard therapy for PAH.This manuscript reviewed the most up-to-date literature on lung transplantation for PAH, focusing particularly on risk stratification, donor allocation, bridging to transplantation (BTT), and intra- and postoperative management in both adult and pediatric patients.The last two decades have witnessed an important shift in the transplant indications and strategy for PAH. Newly introduced antihypertensive drugs have postponed the time of transplantation in eligible patients, thus reserving transplantation for severely ill high-risk patients on triple antihypertensive therapy. Furthermore, the widespread peritransplant use of veno-arterial extracorporeal membrane oxygenation (ECMO) enables cardiac remodeling after bilateral lung transplantation.The change in transplant strategy from combined heart and lung transplantation to bilateral lung transplantation renders more organs available for transplantation in an era of organ shortage. ECMO-bridging is a life-saving tool in selected PAH patients although associated with higher complications. Better organ allocation in PAH patients at high risk of decompensation may reduce the need for ECMO-bridging and may further improve outcomes.
Keywords: transplantation surgery; transplantation; thoracic surgery; long-term survival